The Role of Rumination and Negative Affect in Meaning Making Following Stressful Experiences in a Japanese Sample - Kamijo, Namiko; Yukawa, Shintaro (Frontiers in Psychology, 2018)
Stressful experiences can lead to meaning making that is seen as central in adjustment. Although rumination and negative affect are important factors of meaning making, little is known about the mechanisms involved. This study aimed to examine the meaning making process, focusing on the role of intrusive and deliberate rumination and negative affect. The principal hypotheses were as follows: negative affect is positively related to threat evaluation and intrusive rumination, while regret and guilt are positively related to deliberate rumination; intrusive rumination is negatively related to finding meaning, whereas deliberate rumination is positively related to finding meaning. A total of 383 undergraduate students were asked to remember their most stressful life event and complete a questionnaire containing the Event Related Rumination Inventory and items about negative affect, threat evaluation, and finding meaning about the stressful life event. For 342 of the final sample, structural equation modeling based on the study hypotheses showed that both deliberate and intrusive rumination immediately after the event were positively associated with finding meaning. Intrusive rumination at present, however, was negatively related to finding meaning. This study also revealed the effects of negative affect: helplessness, sadness, and fear induced intrusive rumination; moreover, regret was positively associated with deliberate rumination.